Standard Program For Site Selection Studies In Sweden For A High-Level Nuclear Waste Repository - Hans S. Carlsson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Like most industrial processes, nuclear power production creates wastes, which have to be handled and ultimately disposed of in a safe manner. Some of the wastes contain very long-lived radioactive substances and have to be isolated for very long periods of time before they have decayed to harmless levels. Sweden, like many other countries with similar geology, intends to use crystalline rock for isolating the high-level nuclear waste from the biosphere. The suitability of a rock mass for a repository needs to be investigated extensively. Apart from the political and practical considerations for a site selection, a detailed study has to be performed in terms of geology, hydrogeology, geophysics, geochemistry and rock mechanics. The responsibility of the site selection studies in Sweden is entrusted to the Swedish Nuclear Fuel Supply Company, Division KBS (SKBF/KBS) . The paper gives a brief presentation of the "Standard Program" for the studies that will be carried out during 1980-1990. Modifications of the program are justified on the basis of gained experience or specific circumstances for each site. The program is compiled by the Geological Survey of Sweden (SGU) in cooperation with KBS.